PEMBELAJARAN MENULIS TEKS EKSPLANASI MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ARTICULATE STORYLINE DI KELAS VIII SMP BIMASENA SCHOOL - Ine Sachintania; Eggie Nugraha; Marlia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study is motivated by the low skills and interest of students to write and Indonesian language learning becomes boring, less interesting, and seems monotonous because of the selection of models and media that are not appropriate. This research aims to describe: (1) how students learn to write explanatory texts in Class VIII SMP Bimasena School before using the problem-based learning model assisted by articulate storyline media; (2) how students learn to write explanatory texts in Class VIII SMP Bimasena School after using the problem-based learning model assisted by articulate storyline media; (3) the difference in the ability to write explanatory texts of students in Class VIII SMP Bimasena School in the experimental class and control class using the problem-based learning model assisted by articulate storyline media. The method used, namely pure experiment with pretest-posttest control group design. The results of this study, namely: (1) the value of experimental class students has not met the minimum completeness criteria that have been determined before applying the problem-based learning model assisted by articulate storyline media, this can be proven from the average value and recapitulation of the value that the average pretest of the experimental class is 17.3; (2) the value of experimental class students has met the predetermined minimum completeness criteria after applying the problem-based learning model assisted by articulate storyline media, this can be proven from the average value and recapitulation of the value that the average posttest of the experimental class is 86.5; (3) the experimental class has a higher value compared to the control class after receiving treatment, this can be proven from the recapitulation of the pretest and posttest and seen from the results of the independent sample t-test test, the Sig. (2-tailed) value is 0.001 <0.05.